3(x-4.3)=3.6

Simple and best practice solution for 3(x-4.3)=3.6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-4.3)=3.6 equation:


Simplifying
3(x + -4.3) = 3.6

Reorder the terms:
3(-4.3 + x) = 3.6
(-4.3 * 3 + x * 3) = 3.6
(-12.9 + 3x) = 3.6

Solving
-12.9 + 3x = 3.6

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '12.9' to each side of the equation.
-12.9 + 12.9 + 3x = 3.6 + 12.9

Combine like terms: -12.9 + 12.9 = 0.0
0.0 + 3x = 3.6 + 12.9
3x = 3.6 + 12.9

Combine like terms: 3.6 + 12.9 = 16.5
3x = 16.5

Divide each side by '3'.
x = 5.5

Simplifying
x = 5.5

See similar equations:

| 6/10-4/10 | | 2340=45(p+25) | | 2b+24=-4b+18 | | -6.8(x-2.25)=13.6 | | 6(7x-6)+1=42x-35 | | -6x+8-4(x-1)=-(5x-5)-4x+4 | | 83.2=8(m+3.1) | | 5x+z+6=20 | | 2/3b=8/15 | | .08(y-5)+.06y=.04y-.03(10) | | 5(x+12)=150 | | 7x+8.96=3x+16 | | 1/4-8=6 | | 2(z+8)+16=4 | | 10+3t=-5 | | 2x-2y= 12 | | -[10x-(18x+1)]=1+(7x+10) | | 5/1/5 | | 3x^2+9=-3x | | 2x=5x-63 | | -5(x-5)-4=21 | | 2x-3(4-3x)=3(x-4)-32 | | 3x+49=5x+15 | | -5(6-r)=10 | | 2x+2=4x-80 | | 5x+12=-38-5 | | w(2w+1)=55 | | 4.25x=-46.25 | | 8.73x+1=76.2129+x | | -8x+(-5)=16 | | 12x-53=6x+25 | | -x-4=-2(x-2) |

Equations solver categories